Fourier Transform Infrared (FTIR) Characterization of Sulfate Ion Adsorption on One-Pot Synthesized Quaternary Ammonium Polymer Derived from Vinasse Waste - Sari, Hutri Puspita; Rahayu, Aster; Cahya Hakika, Dhias; Pramia Lestari, Syahrani (Eksergi, 2026)
Vinasse is a major liquid waste generated from the bioethanol industry and contains a high concentration of sulfate ions that may cause environmental problems if not properly managed. This study investigates sulfate adsorption from vinasse wastewater using a one-pot synthesized quaternary ammonium polymer, with a focus on functional group interactions analyzed by Fourier Transform Infrared Spectroscopy (FTIR). Quantitative adsorption experiments were conducted to confirm sulfate removal, while FTIR analysis was employed to examine changes in functional group characteristics before and after adsorption under various operating conditions. The quantitative results demonstrate that sulfate adsorption proceeds rapidly, achieving a removal efficiency of approximately 87.5534% with an adsorption capacity of 10.6800mg/g at a contact time of 20 minutes under the investigated conditions. FTIR spectra indicate that sulfate adsorption does not alter the main polymer structure and is primarily associated with changes in the intensity of bands related to quaternary ammonium groups and sulfate vibrations, suggesting non-covalent interactions dominated by electrostatic attraction, with possible contributions from hydrogen bonding. Overall, this study provides quantitative evidence of sulfate adsorption from real vinasse wastewater and demonstrates the usefulness of FTIR analysis in elucidating interaction behavior between sulfate ions and quaternary ammonium polymer functional groups.